ICTs for agriculture: Making it happen - Pye-Smith, Charlie (Technical Centre for Agricultural and Rural Cooperation, 2014)
The communications revolution provides a unique opportunity to transform the lives of hundreds of millions of farmers in developing countries. With its presentation of the key policy issues discussed at CTA’s ICT4Ag conference, this text provides a valuable insight into how this might be achieved. Issues addressed include developing better partnerships to improve the impact of ICTs in agriculture, strengthening the role of young women and men in ICT initiatives, supporting ICT4Ag entrepreneurship and promoting adequate infrastructure for ICTs in rural areas.